Diffusion Tensor Imaging to Map Brain Microstructural Changes in CADASIL. Issue 1 (30th June 2016) - Mascalchi, Mario; Pantoni, Leonardo; Giannelli, Marco; Valenti, Raffaella; Bianchi, Andrea; Pracucci, Giovanni; Orsolini, Stefano; Ciulli, Stefano; Tessa, Carlo; Poggesi, Anna; Pescini, Francesca; Inzitari, Domenico; et al.
ABSTRACT: BACKGROUND AND PURPOSE: Diffusion tensor imaging (DTI) is sensitive to brain microstructural changes. The aims of this DTI study were to map voxelwise the spatial distribution of brain microstructural changes in patients with cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) and to investigate any correlation between DTI‐derived indices and extension of T2 hyperintensity. METHODS: Eighteen patients with CADASIL and 18 age‐, sex‐, and education‐level‐matched healthy controls underwent magnetic resonance imaging at 3 T. Differences in DTI‐derived indices (mean diffusivity [MD], fractional anisotropy [FA], axial [AD] and radial [RD] diffusivities, and mode of anisotropy [MO]) of brain white matter (WM) between CADASIL patients and healthy subjects were assessed through tract‐based spatial statistics. Then, DTI‐derived indices were correlated with the patient's score on the extended Fazekas visual scale of the T2 hyperintensity. RESULTS: When compared to healthy controls, CADASIL patients showed extensive symmetric areas of increased MD/RD and decreased AD/FA/MO that involved almost the entire hemispheric cerebral WM (internal and external capsule, WM of the temporal poles, superior and inferior longitudinal fasciculus, inferior frontal‐occipital fasciculus, uncinate fasciculus, cingulum, forceps major and minor, corticospinal tracts, and thalamic radiations), thalami, and corpus callosum. Additional areas of increased RD were observed in pons, midbrain, cerebellar peduncles, and cerebellar WM. Only FA was negatively correlated with extended Fazekas visual score. CONCLUSIONS: Our results indicate that brain damage in CADASIL is associated with extensive microstructural changes implying impairment of intra‐ and inter‐hemispheric cerebral, thalamocortical, and cerebrocerebellar connections. Severity of microstructural changes correlates with extension of T2 hyperintensity.